2005
DOI: 10.1158/1078-0432.ccr-04-1293
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Telomerase Activity in Lung Carcinoids Is Dependent on Human Telomerase Reverse Transcriptase Transcription and Alternative Splicing and Is Associated with Long Telomeres

Abstract: Our results indicate that telomerase is repressed in most lung carcinoids and that hTERT transcription and alternative splicing play a role in such a negative regulation. Moreover, the absence of any telomerase maintenance mechanism may contribute to the favorable prognosis of this malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…TA-DMPM did not express any hTERT transcript or, alternatively, displayed the presence of the h -splice variant alone or different combinations of full-length and deletion transcripts, with a generally higher level of alternatively spliced variants compared with that of the complete hTERT transcript. These data would suggest that the presence of the full-length hTERT transcript is necessary but not sufficient to activate the enzyme in DMPM and that not only hTERT transcription but also alternative splicing can contribute to the regulation of TA in this disease, as already reported for melanomas and lung carcinoids (41,42). In this context, we previously showed that forced accumulation of alternatively spliced transcripts with a concomitant decrease of the full-length hTERT, accomplished through the use of 2 ¶-Omethyl-RNA phosphorothioate oligonucleotides targeting the splicing site in the hTERT pre-mRNA, induced a decline of TA in prostate cancer cells (43).…”
Section: Discussionsupporting
confidence: 55%
“…TA-DMPM did not express any hTERT transcript or, alternatively, displayed the presence of the h -splice variant alone or different combinations of full-length and deletion transcripts, with a generally higher level of alternatively spliced variants compared with that of the complete hTERT transcript. These data would suggest that the presence of the full-length hTERT transcript is necessary but not sufficient to activate the enzyme in DMPM and that not only hTERT transcription but also alternative splicing can contribute to the regulation of TA in this disease, as already reported for melanomas and lung carcinoids (41,42). In this context, we previously showed that forced accumulation of alternatively spliced transcripts with a concomitant decrease of the full-length hTERT, accomplished through the use of 2 ¶-Omethyl-RNA phosphorothioate oligonucleotides targeting the splicing site in the hTERT pre-mRNA, induced a decline of TA in prostate cancer cells (43).…”
Section: Discussionsupporting
confidence: 55%
“…This indicates the presence of an active hTERT promoter also in VL-7 cells and suggests that alternative splicing plays a significant role in TA activation of NSCLC cells. Comparably, expression of alternatively spliced hTERT mRNA molecules has been very recently described for TA-and ALT-negative lung carcinoids (53). However, in contrast to our VL-7 cells, these carcinoid cells underwent crisis during in vitro culture, suggesting them as mortal pre-M2 cells comparable with VL-9 NSCLC cells.…”
Section: Discussionsupporting
confidence: 57%
“…Total RNA (0.5 Ag) from each sample was reverse-transcribed by using the reverse transcription-PCR (RT-PCR) Core kit (Applied Biosystems) with random hexamers, and the resultant cDNA was then amplified with the same kit. Amplification of full-length and alternatively spliced human telomerase reverse transcriptase (hTERT) cDNA was obtained as previously described (26).…”
Section: Methodsmentioning
confidence: 99%